Processos de identidade dos indígenas trabalhadores da construção civil na cidade de Boa Vista/RR - Santos, Roseli Bernardo Silva dos (Universidade do Vale do Rio dos Sinos, 2014)
The theme of this thesis is The Identity Processes of the indigenous construction workers in the city of Boa Vista, RR. The work unfolded from the questioning, focusing on the perceived and observed elements regarding to both indigenous peoples and city. We sought to justify this arrangement by the experiences as a teacher and participation in social movements of indigenous peoples. The main objective of the research aimed to understand the issue of indigenous identity in the city from the social interactions. In this process we were able to reflect on ethnic identity and political identity. Its methodological approach is constituted from the qualitative approach followed by ethnographic practice in the light of empirical readings in the resources found in Clifford Geertz and Malinowski, and from this perspective, the field diary was used as a research instrument of greater relevance, which are described after hearing situations and everyday practices observed at the construction sites. Through the concomitant oral reports observations, elements pointed in the ancestries that comprise the cultural universe were found, set mainly by cosmologies, which remain in their experiences in the city. We interviewed nine indigenous workers, among them, helpers mason, masons and master builders, and besides them we searched for information with supporting actors, which contributed with specific information for the investigative development. The readings of the captured images at the work sites and at other spaces allowed us to register various situations, especially during the workday. Then we point the analysis of city space in the lives of indigenous peoples before the exploitation processes of these people in the labor world. The body of the research is divided into four chapters, followed by the synthesis of the historical process of the labor of the indigenous peoples, since the period of colony and empire in the northern Amazon region to the Rio Branco region, known as Roraima nowadays, the encounter between indigenous actors and the state: the processes of identity beyond the walls of the city, perceptions of indigenous peoples in the city: the experiences in Boa Vista, Roraima and Indian construction workers in Boa Vista, Roraima: an ethnographic spatial context, knowledge and beliefs in the labor world. We have considered that the thesis is based on the idea of the identity process of the indigenous construction workers.
Keywords: Índios; Trabalhadores; Construção civil; Processo de identidade; Indigenous peoples; Workers; Construction; Identit y process; ACCNPQ::Ciências Humanas::Sociologia